Fallopian tube cancer incidentally diagnosed during laparoscopy for metastatic adenocarcinoma of unknown primary lesion - Mayumi Takano; Yukiko Kagawa; Susumu Murata; Michihisa Fujiwara; Masahiko Nakata; Yasumasa Monobe; Mitsuru Shiota (Wolters Kluwer Medknow Publications, 2016)
Primary fallopian tube cancer is a rare gynecological malignancy. We report a case of fallopian tube cancer that was incidentally diagnosed during laparoscopy for metastatic adenocarcinoma of unknown primary lesion. A 60-year-old woman had two intraperitoneal calcific masses, which a biopsy revealed to be a metastatic malignancy with an unknown primary site. She was asymptomatic, and the primary site was not identified in imaging evaluations such as transvaginal ultrasonography. A diagnostic laparoscopy was performed and revealed papillary tumor-like lesions in the right fallopian tube. The laparoscopy was immediately converted to laparotomy. Total hysterectomy, bilateral salpingo-oophorectomy, and an omentectomy were also performed. The histopathologic diagnosis was primary serous adenocarcinoma of the fallopian tube. The patient received adjuvant chemotherapy. At 8 months postoperatively, there were no signs of recurrence. In this patient, the diagnostic laparoscopy was more useful for detecting the primary small-volume fallopian tube cancer, compared with ultrasonography, computed tomography (CT), magnetic resonance imaging, and positron emission tomography-computed tomography (PET-CT). Laparoscopy may be a tool for revealing an obscure primary lesion in the abdominal cavity.